2010
DOI: 10.1117/12.852526
|View full text |Cite
|
Sign up to set email alerts
|

High-performance long wave infrared bolometer fabricated by wafer bonding

Abstract: A novel microbolometer with peak responsivity in the longwave infrared region of the electromagnetic radiation is under development at Sensonor Technologies. It is a focal plane array of pixels with a 25µm pitch, based on monocrystalline Si/SiGe quantum wells as IR sensitive material. The novelty of the proposed 3D process integration comes from the choice of several of the materials and key processes involved, which allow a high fill factor and provide improved transmission/absorption properties. Together wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…For a given pixel pitch, there are several design issues relating to both the sensor material and the sensor-to-ROIC integration process that must be considered to reach overall good performance. We have previously reported on some aspects of sensor material design and optimization [6,7] and on the integration process for 25x25 µm pitch pixels [8][9][10]. In this paper we will address further design aspects of the infrared absorbing internal quarter wave cavity and present the latest results on scaling of the heterogeneous integration process down to 17x17 µm pitch bolometer arrays.…”
Section: Introductionmentioning
confidence: 99%
“…For a given pixel pitch, there are several design issues relating to both the sensor material and the sensor-to-ROIC integration process that must be considered to reach overall good performance. We have previously reported on some aspects of sensor material design and optimization [6,7] and on the integration process for 25x25 µm pitch pixels [8][9][10]. In this paper we will address further design aspects of the infrared absorbing internal quarter wave cavity and present the latest results on scaling of the heterogeneous integration process down to 17x17 µm pitch bolometer arrays.…”
Section: Introductionmentioning
confidence: 99%
“…All our work has been on Si substrates with electroplated layers, typically 5 μm Cu and 1-2 μm Sn. For wafer-level bonding, equal layer thicknesses on both bonding partners have been used, and the bonding profile (temperature and pressure vs. time) has been carefully selected to allow flux-free bonding [2,18]. For the initial chip-bonding, Sn has been electroplated only on the chip side, in order to allow maintaining the substrate hot (no Cu-Sn interdiffusion prior to bonding) while mounting successive Sn-coated chips.…”
Section: Fabrication Processmentioning
confidence: 99%
“…Their TCR (Temperature Coefficient of Resistance) is usually between -2%/K and -4%/K [1-2]. It was shown that quantum wells can be used as thermistors with TCR of 3%1K and 978-1-4799-3570-3/13/$31.00 ©2013 IEEE with values of over 4%/K considered attainable after optimization of the structure [3]. Diodes can also be used as sensitive element with even higher temperature dependency, up to 7%/K [4].…”
Section: Introductionmentioning
confidence: 99%